Switching subtype-selectivity: Fragment replacement strategy affords novel class of peroxisome proliferator-activated receptor α/δ (PPARα/δ) dual agonists. Issue 14 (15th July 2017) - Shioi, Ryuta; Okazaki, Shogo; Noguchi-Yachide, Tomomi; Ishikawa, Minoru; Makishima, Makoto; Hashimoto, Yuichi; Yamaguchi, Takao
Graphical abstract: Abstract: Peroxisome proliferator-activated receptors (PPARs) are important drug targets for treatment of dyslipidemia, type 2 diabetes, cardiovascular disease, nonalcoholic fatty liver disease and nonalcoholic steatohepatitis, and great efforts have been made to develop novel PPAR ligands. However, most existing PPAR ligands contain a carboxylic acid (CA) or thiazolidinedione (TZD) structure (acidic head group) that is essential for activity. We recently discovered non-CA/TZD class PPARα/δ partial agonists, which contain an acetamide moiety and adjacent methyl group, linked to a 1, 2, 4-oxadiazole ring ("fragment a"). We hypothesized that the acetamide structure might interact with the CA/TZD-binding pocket. To test this idea, we firstly replaced fragment a in one of our compounds with the α-alkoxy-CA structure often found in PPAR agonists. Secondly, we replaced the α-alkoxy-CA head group of several reported PPAR agonists with our acetamide-based fragment a. The agonistic activities of the synthesized hybrid compounds toward PPARs (PPARα, PPARγ and PPARδ) were evaluated by means of cell-based reporter gene assays. All the hybrid molecules showed PPAR-agonistic activities, but replacement of the α-alkoxy-CA head group altered the maximum efficacy and the subtype-specificity. The acetamide-based hybrid molecules showed partial agonism toward PPARα and PPARδ, whereas the α-alkoxy-CA-based molecules were generally selective for PPARα and PPARγ, with relatively high activation efficacies. Thus, the fragment replacement strategy appears promising for the development of novel acetamide-based PPARα/δ dual agonists.